2009
DOI: 10.1111/j.1742-4658.2009.06990.x
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the folding mechanism of the 52‐knotted protein UCH‐L3

Abstract: Proteins possessing deeply embedded topological knots in their structure add a stimulating new challenge to the already complex protein‐folding problem. The most complicated knotted topology observed to date belongs to the human enzyme ubiquitin C‐terminal hydrolase UCH‐L3, which is an integral part of the ubiquitin–proteasome system. The structure of UCH‐L3 contains five distinct crossings of its polypeptide chain, and it adopts a 52‐knotted topology, making it a fascinating target for folding studies. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 41 publications
7
71
0
Order By: Relevance
“…It was found that the threaded dimer folded about an order of magnitude more slowly than the wild-type protein, in which threading is not required during folding since both chains of the dimer are linear (22). Our observation of a complex energy landscape for 2ouf-knot is also consistent with recent experimental investigations of the folding pathways of naturally knotted proteins (11,23); all three of the proteins studied have been found to fold very slowly, with complex kinetic behaviors involving multiple intermediates. The lack of unknotted controls for those proteins has prevented direct assessment of the role played by their knotted topologies.…”
Section: Discussionsupporting
confidence: 79%
“…It was found that the threaded dimer folded about an order of magnitude more slowly than the wild-type protein, in which threading is not required during folding since both chains of the dimer are linear (22). Our observation of a complex energy landscape for 2ouf-knot is also consistent with recent experimental investigations of the folding pathways of naturally knotted proteins (11,23); all three of the proteins studied have been found to fold very slowly, with complex kinetic behaviors involving multiple intermediates. The lack of unknotted controls for those proteins has prevented direct assessment of the role played by their knotted topologies.…”
Section: Discussionsupporting
confidence: 79%
“…The unfolding kinetics of wild-type and mutant UCH-L1 were measured by stopped-flow techniques for shorter timescales or by manual mixing with a fluorometer for longer timescales, as previously described 20 (further details are available in Supporting Information).…”
Section: Unfolding Kineticsmentioning
confidence: 99%
“…Earlier experimental investigations of the folding of UCH-L3, a homolog of UCH-L1, showed that it folds via parallel pathways, each of which exhibits a hyperfluorescent intermediate state (27). Researchers have investigated wildtype (WT) UCH-L1 using a range of different techniques.…”
Section: Introductionmentioning
confidence: 99%